Hypercalcemia Associated With Severe Dysphagia in a Patient With Parathyroid Adenoma and Significant Cervical Spondylophytes - Duje Čulina, MD; Mirta Peček, MD; Tomislav Gregurić, MD, PhD; Ivana Aras, MD, PhD; Andro Košec, MD, PhD, FEBORL-HNS; Siniša Stevanović, MD, PhD (AACE Clinical Case Reports, 2024)
Background/Objective: Severe dysphagia is a rare presenting symptom of primary hyperparathyroidism, whereas the most common hypercalcemia-related causes include gastrointestinal symptoms, such as anorexia, constipation, and pancreatitis. This case presentation aimed to describe swallowing difficulty as a leading symptom of hypercalcemia. Case Report: A 62-year-old man experienced vomiting, dysphagia bordering with aphagia, and 20-kg weight loss in a 2-month period. The parathyroid hormone and serum calcium levels were 102 pmol/L (reference range, 1.8-7.9 pmol/L) and 4.12 mmol/L (reference range, 2.14-2.53 mmol/L), respectively. Ultrasound-guided exploration of the neck revealed a large, rounded hypoechoic mass inferior to the left thyroid lobe, which contained parathyroid tissue on fine-needle aspiration cytology examination. Contrast-enhanced neck computed tomography revealed a mass measuring 3.6 × 2.6 × 2.5 cm behind the left thyroid lobe, alongside massive ventral spondylophytes of the cervical spine at the level of the postcricoid segment of the hypopharynx. Magnetic resonance imaging confirmed ventral tissue displacement due to spondylophyte size and location. Surgical exploration of the left side of the neck was performed, and the left lower parathyroid gland weighing 9.07 g was excised. Pathohistologic findings verified a parathyroid gland adenoma. The postoperative values showed parathyroid hormone and serum calcium levels at 4.54 pmol/L and 2.25 mmol/L, respectively. Discussion: The pathophysiology of dysphagia in hypercalcemia is not fully elucidated. In this case, the patient’s improvement after surgery implies a plausible connection between hypercalcemia and dysphagia, suggesting a causal relationship. Conclusion: Although aphagia is not a typical presenting symptom of parathyroid adenoma, it should be noted in the differential diagnosis.